2022
DOI: 10.30541/v48i4iipp.921-938
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Dynamics of Sugar Industry of Pakistan.

Abstract: Pakistan is the 15th largest producer of sugar in the world, 5th largest in terms of area under sugar cultivation and 60th in yield. The sugar industry is the 2nd largest agro based industry which comprises of 81 sugar mills. With this scenario, Pakistan has to import sugar which exposes it to the effects of shortage and rising prices in the world. The present sugar crisis has opened up new avenues for researcher to analyse the performance and efficiency of the firms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, income is an essential component of well-being but income alone cannot account for well-being. Haq (2009) measured human well-being in Pakistan and found that human well-being can be understood and measured in four domains: economics, education, living conditions, and health. The study was focused on subjective and objective dimensions of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, income is an essential component of well-being but income alone cannot account for well-being. Haq (2009) measured human well-being in Pakistan and found that human well-being can be understood and measured in four domains: economics, education, living conditions, and health. The study was focused on subjective and objective dimensions of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Beaumont (2011) found that adults with higher levels of educational qualification were more likely to have higher levels of satisfaction with their quality of life; therefore, there was a positive relationship between education and well-being. Haq (2009) measured human well-being in Pakistan and found that human well-being can be understood and measured in four domains: economics, education, living conditions and health. The study was focused on subjective and objective dimensions of well-being.…”
Section: Literature Reviewmentioning
confidence: 99%